A Short Discussion Paper on the Lesotho Food Crisis - (:unkn) unknown (My University, 2003)
In the media, the term drought is being used almost interchangeably with famine in the context of the current southern African food crisis. Lesotho is cited as one of the countries affected by food insecurity and was the first to declare a national emergency. But what is the real picture in Lesotho, how much is the current food insecurity caused by drought compared with other longer term factors?.
Keywords: African Research